In-service teachers’ readiness to conduct action research - Abuabdou, Heba; Badrasawi, Kamal J I (2020)
Teachers are required to be researchers. A research project is being conducted to investigate the readiness of in-service school teachers to conduct action research using the mixed method research design. This paper is allocated to present the validation process of the self-developed research survey. Five experts from three Faculties of Education examined the content and face validity of the survey. The survey was improved and modified based on the given comments. Then, the survey was piloted on 49 in-service Mathematics teachers in Gaza Strip, Palestine. The alpha coefficient for the final 38 items was 0.928, suggesting that the items have high internal consistency. In conclusion, the instrument is valid and reliable to be used in the final data collection.